2019
DOI: 10.3390/microorganisms7090297
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiology of Aspergillus Fumigatus Endophthalmitis in Immunocompetent and Immunocompromised Mice

Abstract: Despite Aspergillus being the leading cause of exogenous fungal endophthalmitis following traumatic injury to the eye, its pathogenesis is not fully understood. In the current study, we developed a murine model of Aspergillus fumigatus (AF) endophthalmitis and investigated the disease pathobiology. Endophthalmitis was induced by intravitreal injection of Aspergillus spores in immunocompetent and immunocompromised (neutropenic) C57BL/6 mice, and disease severity was assessed by eye exam, fungal burden estimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 63 publications
(86 reference statements)
1
24
1
Order By: Relevance
“…Additionally, we noticed that A. flavus causes a downregulation in the levels of GM-CSF and IFN-γ in microglia cells, which was similar to the findings by Schneider et al [43] who reported that A. fumigatus actively impairs the release of IFN-γ (and M-CSF) by NK cells. In contrast to the results obtained regarding the cytokine expression in the murine model of Aspergillus endophthalmitis [14], where the production of several inflammatory mediators including IL-1β, IL6, and CXCL2 were reported, we observed a nonsignificant downregulation of IFN-γ and IL-1β. Numerous observations that IL-17 contributes to fungal protection have been obtained from studies with experimental models of infection [44].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Additionally, we noticed that A. flavus causes a downregulation in the levels of GM-CSF and IFN-γ in microglia cells, which was similar to the findings by Schneider et al [43] who reported that A. fumigatus actively impairs the release of IFN-γ (and M-CSF) by NK cells. In contrast to the results obtained regarding the cytokine expression in the murine model of Aspergillus endophthalmitis [14], where the production of several inflammatory mediators including IL-1β, IL6, and CXCL2 were reported, we observed a nonsignificant downregulation of IFN-γ and IL-1β. Numerous observations that IL-17 contributes to fungal protection have been obtained from studies with experimental models of infection [44].…”
Section: Discussioncontrasting
confidence: 99%
“…Understanding the available information on how microglial cells react and influence disease progression in fungal infections is important and warrants further investigation to mitigate the number of clinical cases of patients with fungal endophthalmitis not responsive to standard therapy [12]. Additionally, a previous 25 year study at our institute found the filamentous fungus Aspergillus flavus (A. flavus) as one of the most clinically relevant fungal pathogens [13] which is a less studied organism compared to its related and well known human pathogen, A. fumigatus [14][15][16]. The purpose of the present study was to study the hypothesis that microglia cells would have a differential inflammatory response to infection by C. albicans and A. flavus isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from our lab, as well as by other investigators, have shown that the severity of endophthalmitis is strongly correlated with intraocular inflammation, characterized by the infiltration of neutrophils and production of inflammatory cytokines. 35,[37][38][39]49,58 In general, due to differences in sex hormones, males present Th1 dominance by producing TNF-α, IL-1β, and IL-6 cytokines, whereas females activate a Th2 response and produce high levels of interleukins (IL-4, IL-5, and IL-10) in response to infection. 21,[59][60][61][62][63] Here, our sex-based analysis did not reveal any significant difference in the production of inflammatory mediators and neutrophil infiltration in the infected eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry was used to determine the infiltration of PMNs as described previously. 6 , 41 , 42 Briefly, following euthanasia, retinas were isolated from CA infected and control mice at desired time points. To obtain a sufficient number of cells, two retinas were pooled for each time point and immediately digested with Accumax (Millipore) for 10 minutes at 37°C then triturated by passing through a 23-gauge needle/syringe to make a single-cell suspension.…”
Section: Methodsmentioning
confidence: 99%
“…Although bacterial endophthalmitis is far more common than fungal endophthalmitis, 4 , 5 fungal infections still pose a serious challenge to ophthalmologists due to lack of differential diagnosis and limited treatment options. 6 The incidence of fungal endophthalmitis varies greatly and depends on several factors such as the use of total parenteral nutrition, broad-spectrum antibiotics, recent abdominal surgery, neutropenia, glucocorticoid therapy in inpatients, and both intravenous drug use (IVDU) and recent central venous catheters, which includes peripherally inserted central catheters (PICC lines) in outpatients. 7 In the United States and Europe, fungal endophthalmitis is less common, whereas in India and China, it can account for 10% to 20% of all cases of endophthalmitis.…”
mentioning
confidence: 99%